The Use of the Father Image in Imperial Propaganda and 1 Corinthians 4:14-21 - Lassen, Eva Maria (Tyndale bulletin, 1991)
This article explores one aspect of the use of family metaphors in early Christianity: the father-concept used metaphorically by Paul to assert his apostolic authority in the Corinthian church.